Squamous Cell Carcinoma Biomarker Sensing on a Strontium Oxide-Modified Interdigitated Electrode Surface for the Diagnosis of Cervical Cancer - Wang, Hongqing; Lakshmipriya, Thangavel; Chen, Yeng; Gopinath, Subash Chandra Bose (Hindawi Publishing Corporation, 2019)
Cervical cancer is a life-threatening complication, appearing as the uncontrolled growth of abnormal cells in the lining of the cervix. Every year, increasing numbers of cervical cancer cases are reported worldwide. Different identification strategies were proposed to detect cervical cancer at the earlier stages using various biomarkers. Squamous cell carcinoma antigen (SCC-Ag) is one of the potential biomarkers for this diagnosis. Nanomaterial-based detection systems were shown to be efficient with different clinical biomarkers. In this study, we have demonstrated strontium oxide-modified interdigitated electrode (IDE) fabrication by the sol-gel method and characterized by scanning electron microscopy and high-power microscopy. Analysis of the bare devices indicated the reproducibility with the fabrication, and further pH scouting on the device revealed that the reliability of the working pH ranges from 3 to 9. The sensing surface was tested to detect SCC-Ag against its specific antibody; the detection limit was found to be 10 pM, and the sensitivity was in the range between 1 and 10 pM as calculated by 3σ. The specificity experiment was carried out using major proteins from human serum, such as albumin and globulin. SCC-Ag was shown to be selectively detected on the strontium oxide-modified IDE surface. © 2019 Hongqing Wang et al.